Expert systems in production and services : form asssessment to action? - International Workshop on Expert Systems in Production and Services (2nd : 1988 : Chicago, Ill.); Bernold, Thomas; Hillenkamp, Ulrich (New York : Elsevier, 1988)
Includes bibliographical references.